NARRATIVE OF RELIGIOUS MODERATION IN LOCAL MEDIA: HOW DOES SOLOPOS PROMOTE WASATHIYAH JOURNALISM? - Mokhamad Zainal Anwar; Abraham Zakky Zulhazmi; Nur Rohman; Abd Halim (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2023)
Although many agencies have carried out campaigns for and socialization of religious moderation, cases of intolerance still occur locally. These socialization agents are religious groups and university academics, and the media play a significant role because they produce information and influence people's perceptions to take action. This study uses a qualitative descriptive method with Stuart Hall's content analysis. Hall believed that meaning is constructed through language. Meanwhile, the primary data source is religious moderation narrative articles published in the Solopos. This paper aims to describe the discourse on religious moderation produced by Solopos, published every Friday through the Khazanah rubric from March 2020 to March 2022. This research focuses on three aspects: firstly, who are the agencies used as references by the Solopos media in producing moderation narratives?; secondly, what are the issues contained in the Khazanah rubric?; and thirdly, how does the editorial policy present the discourse of religious moderation in Khazanah rubric? The conclusions of this study are: Firstly, Solopos uses teachers, lecturers, and religious leaders as references. They come from Islamic organizations such as NU and Muhammadiyah. Secondly, the issue of religious moderation raised by Solopos revolves around fiqh, muamalah, and aqidah. Thirdly, the editor of Solopos is committed to maintaining harmony by continuing to display articles that reflect moderate Islam. We call the journalism practice implemented by Solopos through the Khazanah rubric the wasathiyah journalism.